2014
DOI: 10.1007/s40291-013-0080-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Biofilm Production of Yersinia enterocolitica Strains Isolated from Infected Children and Comparative Antimicrobial Susceptibility of Biofilm Versus Planktonic Forms

Abstract: These results, indicate that biofilm formation by Y. enterocolitica might be an inherent feature. The presence of biofilms increased dramatically the MICBR in all antimicrobials. The way in which biofilms could contribute to Y. enterocolitica pathogenicity in humans is a matter needing further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
3
17
1
Order By: Relevance
“…Our results showed that the capacity to form biofilms among the Y. enterocolitica examined strains could be a strain‐related feature. Although, some authors reported that all Y. enterocolitica strains examined in their studies had produced biofilms(Ioannidis et al 2014; Singhal et al 2019), our results are in accordance with other studies that showed differences in biofilm formation among the examined strains (Wang et al 2017; Zadernowska and Chajęcka‐Wierzchowska 2017; Younis et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the capacity to form biofilms among the Y. enterocolitica examined strains could be a strain‐related feature. Although, some authors reported that all Y. enterocolitica strains examined in their studies had produced biofilms(Ioannidis et al 2014; Singhal et al 2019), our results are in accordance with other studies that showed differences in biofilm formation among the examined strains (Wang et al 2017; Zadernowska and Chajęcka‐Wierzchowska 2017; Younis et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Although little has been published about the role of biofilms and the factors leading to biofilm formation in Y. enterocolitica , it has been well established that flagella play a critical role at the beginning of the biofilm formation (Liaqat et al 2018). Furthermore, Y. enterocolitica strains able to form biofilms have presented enhanced antibiotic resistance (Ioannidis et al 2014). Quorum sensing system in most of Gram‐negative bacteria is LuxI/LuxR‐type, corresponding to the acil‐homoserine lactones (AHL, a type of inductors) synthase and the response regulator (Shaaban et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The survival of Y. enterocolitica in the environment, including water environments, is also increased by the ability of Y. enterocolitica to form biofilms (Ioannidis et al 2014). The ability to form biofilms may allow microorganisms to persist in the environment and to resist desiccation and treatment with antimicrobial agents and disinfectants.…”
Section: Microflora Of Fish and Fish Environmentsmentioning
confidence: 99%
“…However, researchers isolated Y. enterocolitica biofilm from infected children and determined that antibiotic resistance was enhanced in the biofilm (Ioannidis et al . ). Another study found that monoacylglycerol exerted an inhibitory effect on Y. enterocolitica biofilm (Ham and Kim ).…”
Section: Introductionmentioning
confidence: 97%